Investigating the Mechanism of Sodium Binding to SERT Using Direct Simulations - Szöllősi, Dániel; Stockner, Thomas (Frontiers in Cellular Neuroscience, 2021)
The serotonin transporter (SERT) terminates neurotransmission by transporting serotonin from the synapse into the pre-synaptic nerve terminal. Altered SERT function leads to several neurological diseases including depression, anxiety, mood disorders and attention deficit hyperactivity disorders (ADHD). Accordingly is SERT the target for their pharmacological treatments, but also targeted by multiple drugs of abuse. Transport of serotonin by SERT is energized by the transmembrane electrochemical gradient of sodium. We used extensive molecular dynamics simulations to investigate the process of sodium binding to SERT, which is the first step in the transport cycle that leads to serotonin uptake. Comparing data from 51 independent simulations, we find a remarkably well-defined path for sodium entry and could identify two transient binding sites, while observing binding kinetics that are comparable to experimental data. Importantly, structure and dynamics of the sodium binding sites indicate that sodium binding is accompanied by an induced fit mechanism that leads to new conformations and reduces local dynamics.